Advances in the biogeographical and ecological knowledge of the genus Quercus (Fagaceae) in Michoacán, Mexico - Uribe-Salas, Dolores; España-Boquera, María Luisa; Torres Miranda, Andrés (Instituto de Ecología, A.C., 2018)
Background and Aims:Michoacan is a state with high biodiversity. Taxonomic studies estimate that there are 30 to 37 species of oak in the state; however, there is scarce information about their distribution patterns. In this study, the geographic and ecological distribution patterns of the genus, and its two sections, composed of 33 species (1734 records), were analyzed at municipality level; topographic, climatic, edaphic, and ecological data are included.Methods: Indices of richness, rarity and irreplaceability were calculated to obtain the distribution patterns at the municipal level of genus and both sections. Cluster analyses were performed to identify patterns of geographic, ecologic and elevational distribution of the species. It was tested whether any environmental gradient explains the distributional patterns.Key results: The highest specific richness of the Quercus genus is located in the Trans-Mexican Volcanic Belt (TMVB) and Sierra Madre del Sur (SMS), where humid and subhumid temperate environments are prevalent; the highest rareness occurred in the east-northeast of the TMVB. With respect to elevation, section Quercus shows larger distribution ranges than section Lobatae. Based on elevation, the oaks can be classified into low (600-1900 m a.s.l.) and high mountains (2000-3100 m a.s.l.) with a strong turnover of species between 1900-2000 m a.s.l. Five groups of species are identified, based on their environmental similarity, which coincide with physiographic regions.Conclusions: The municipal richness of oaks is correlated with topographic and aridity heterogeneity at the generic level, mainly in the Lobatae section. Considering that greater environmental heterogeneity corresponds to a greater diversity of species, it is recommended to increase the sampling effort in municipalities that have greater environmental heterogeneity. Intensive fieldwork in the SMS is suggested. There are still unresolved taxonomic problems that should be studied in detail.